2016
DOI: 10.1007/398_2016_8
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Bioavailability, Uptake, Toxicity and Detoxification in Soil-Plant System

Abstract: This review summarizes the findings of the most recent studies, published from 2000 to 2016, which focus on the biogeochemical behavior of Cd in soil-plant systems and its impact on the ecosystem. For animals and people not subjected to a Cd-contaminated environment, consumption of Cd contaminated food (vegetables, cereals, pulses and legumes) is the main source of Cd exposure. As Cd does not have any known biological function, and can further cause serious deleterious effects both in plants and mammalian cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
193
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 231 publications
(199 citation statements)
references
References 426 publications
(458 reference statements)
5
193
0
1
Order By: Relevance
“…Physiological studies revealed that enhanced metal xylem loading and transfer to the aerial plant parts is mediated by carrier proteins (Ali et al, 2013;Shahid et al, 2016). Several studies have recently revealed that the transporters proteins like CDF (cation diffusion facilitator), ZIP [zinc-regulated transporter proteins (ZRTP), Iron-regulated transporter proteins (IRTP)], HMA (heavy metal(loid) ATPase) and Nramp (natural resistance and macrophage protein) are associated with the enhanced transfer of heavy metal(loid)s to aerial tissues in hyperaccumulator plant species (Ovečka and Takáč, 2014;.…”
Section: Phytoremediationmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiological studies revealed that enhanced metal xylem loading and transfer to the aerial plant parts is mediated by carrier proteins (Ali et al, 2013;Shahid et al, 2016). Several studies have recently revealed that the transporters proteins like CDF (cation diffusion facilitator), ZIP [zinc-regulated transporter proteins (ZRTP), Iron-regulated transporter proteins (IRTP)], HMA (heavy metal(loid) ATPase) and Nramp (natural resistance and macrophage protein) are associated with the enhanced transfer of heavy metal(loid)s to aerial tissues in hyperaccumulator plant species (Ovečka and Takáč, 2014;.…”
Section: Phytoremediationmentioning
confidence: 99%
“…Hyperaccumulator plants are capable to sequester and/or bind metals to vacuole to prohibit their otherwise toxic effects. In plants, some natural chelates such as phytochelatins (PCs), GSH and metallothioneins (MTs) are characterised as the best metal-chelating ligands for sequestration of metal(loid)s to vacuoles, and are main part of the metal detoxification system in plants (Ali et al, 2013;Shahid et al, 2016;Adrees et al, 2015). Heavy metal(loid)s complexation with MTs, GSH and PCs is an effective way to neutralise the toxic effects of metals, most likely because the metal-PC complexes are transferred and sequestered in the cell vacuole (Yadav, 2010).…”
Section: Phytoremediationmentioning
confidence: 99%
“…Cadmium occurs at +2 oxidation state, and easily forms complex cataions and anions, especially with Cl, S, and OH, It exhibits chalcophilic properties and behaves very similar to Zn, but has a stronger at finity for S, and is more mobile in acidic environments (Kabata-Pendias and Szteke, 2015). Cd ranks as the 65 the most abundant elements in the Earth's crust (Shahid et al, 2016), While cd can be found together with the Zn ore sphalerite, greewockite (cds) is the only known Cd-based ore (Rao et al, 2011). Human exposure to cadmium in excessive concentrations has the potential to cause, bone lesions, lung insufficiency, cancer, erotogenic effects, renal (disturbances, anemia, hypertension and weight loss (Alina Kabata-Pendias, 2011), Because of it's potential to cause such adverse effects, cd is classed as potential human carcinogen (group2B) by the Us Environmental Protection Agency (EPA), human carcinogen (group1) by the International Agency for Research on cancer of the world Health organization (WHO) (Shahid et al, 2016), and ranked No.7 among the top 20 priority hazardous substances by the Agency for Toxic substances and Disease Registry (ATSDR, 2012)of all the non-essential heavy metals, cadmium (cd) is perhaps the metal which has attracted most attention in soil science and plant nutrition due to its potential toxicity to man, and the relative mobility in the soil-plant system (McLaughlin and Singh, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Cd ranks as the 65 the most abundant elements in the Earth's crust (Shahid et al, 2016), While cd can be found together with the Zn ore sphalerite, greewockite (cds) is the only known Cd-based ore (Rao et al, 2011). Human exposure to cadmium in excessive concentrations has the potential to cause, bone lesions, lung insufficiency, cancer, erotogenic effects, renal (disturbances, anemia, hypertension and weight loss (Alina Kabata-Pendias, 2011), Because of it's potential to cause such adverse effects, cd is classed as potential human carcinogen (group2B) by the Us Environmental Protection Agency (EPA), human carcinogen (group1) by the International Agency for Research on cancer of the world Health organization (WHO) (Shahid et al, 2016), and ranked No.7 among the top 20 priority hazardous substances by the Agency for Toxic substances and Disease Registry (ATSDR, 2012)of all the non-essential heavy metals, cadmium (cd) is perhaps the metal which has attracted most attention in soil science and plant nutrition due to its potential toxicity to man, and the relative mobility in the soil-plant system (McLaughlin and Singh, 1999). Cadmium is produced mainly as a by-product in mining and refining of Zn, therefore its supply is more dependent on the Zn production than on the cd demand, cadmium is also recovered from recycled materials such as Zn-cd batteries (Kabata-Pendias and Mukherjee, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This statement necessitates the research of its toxic effect mechanisms on plant organisms and determination of the physiological and biochemical adaptive changes in plant cell metabolism [3,4].Plants resistance ability to the high environmental concentrations of cadmium depends on: plant genotype, stage of development and metal concentration, and it is achieved by activation of the induced resistance mechanisms [5]. The support of antioxidant status appropriate level and plant cell ability to the cadmium ions chelation are considered as one of the main intracellular mechanisms of plant resistance to toxic cadmium effect [6].…”
mentioning
confidence: 99%